No Evidence of Hendra Virus Infection in the Australian Flying‐fox Ectoparasite Genus Cyclopodia. (22nd October 2016) - Vidgen, M. E.; Edson, D. W.; van den Hurk, A. F.; Field, H. E.; Smith, C. S.
Summary: Hendra virus (HeV) causes potentially fatal respiratory and/or neurological disease in both horses and humans. Although Australian flying‐foxes of the genus Pteropus have been identified as reservoir hosts, the precise mechanism of HeV transmission has yet to be elucidated. To date, there has been limited investigation into the role of haematophagous insects as vectors of HeV. This mode of transmission is particularly relevant because Australian flying‐foxes host the bat‐specific blood‐feeding ectoparasites of the genus Cyclopodia (Diptera: Nycteribiidae), also known as bat flies. Using molecular detection methods, we screened for HeV RNA in 183 bat flies collected from flying‐foxes inhabiting a roost in Boonah, Queensland, Australia. It was subsequently demonstrated that during the study period, Pteropus alecto in this roost had a HeV RNA prevalence between 2 and 15% (95% CI [1, 6] to [8, 26], respectively). We found no evidence of HeV in any bat flies tested, including 10 bat flies collected from P. alecto in which we detected HeV RNA. Our negative findings are consistent with previous findings and provide additional evidence that bat flies do not play a primary role in HeV transmission.